Evidence-Based Alignment of Pathology Residency With Practice II: Findings and Implications - W. Stephen Black-Schaffer MD; Stanley J. Robboy MD; David J. Gross PhD; James M. Crawford MD, PhD; Kristen Johnson PhD; Melissa Austin MD; Donald S. Karcher MD; Rebecca L. Johnson MD; Suzanne Z. Powell MD; Joseph Sanfrancesco MD; Michael B. Cohen MD (Elsevier, 2021)
This article presents findings from a 4-year series of surveys of new-in-practice pathologists, and a survey of physician employers of new pathologists, assessing how pathology graduate medical education prepares its graduates for practice. Using the methodology described in our previous study, we develop evidence for the importance of residency training for various practice areas, comparing findings over different practice settings, sizes, and lengths of time in practice. The principal findings are (1) while new-in-practice pathologists and their employers report residency generally prepared them well for practice, some areas-billing and coding, laboratory management, molecular pathology, and pathology informatics-consistently were identified as being important in practice but inadequately prepared for in residency; (2) other areas-autopsy pathology, and subspecialized apheresis and blood donor center blood banking services-consistently were identified as relatively unimportant in practice and excessively prepared for in residency; (3) the notion of a single comprehensive model for categorical training in residency is challenged by the disparity between broad general practice in some settings and narrower subspecialty practice in others; and (4) the need for preparation in some areas evolves during practice, raising questions about the appropriate mode and circumstance for training in these areas. The implications of these findings range from rebalancing the emphasis among practice areas in residency, to reconsidering the structure of graduate medical education in pathology to meet present and evolving future practice needs.